Gender differences in occupational employment. - Wootton, Barbara H. (Monthly Labor Review, 1997)
The writer presents an analysis of the gender differences in occupational employment. Occupational differences between women and men stayed in decline between 1985 and 1995, although at a somewhat slower pace than during the 1970s and the 1980s. Changes in the gender composition within occupations accounted for a bigger share of the fall in occupational segregation during 1985 to 1995 than did changes in the occupational mix of the workforce. Employment in many particular occupations became less dominated by one sex, although the gender concentration of some particular jobs grew over the period. Nonetheless, major differences in occupational employment still exist, and the extent of these differences varies by a number of factors, such as educational achievement and age.